Artificial Intelligence Applications and Innovations c - Papadopoulos, Harris; Andreou, Andreas S.; Iliadis, Lazaros; Maglogiannis, Ilias; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 9th IFIP WG 12.5 International Conference on Artificial Intelligence Applications and Innovations, AIAI 2013, held in Paphos, Cyprus, in September/October 2013. The 26 revised full papers presented together with a keynote speech at the main event and 44 papers of 8 colocated workshops were carefully reviewed and selected for inclusion in the volume. The papers of the main event are organized in topical sections on data mining, medical informatics and biomedical engineering, problem solving and scheduling, modeling and decision support systems, robotics, and intelligent signal and image processing.
Data mining, medical informatics and biomedical engineering -- Problem solving and scheduling -- Modeling and decision support systems -- Robotics -- Intelligent signal and image processing.
Keywords: Computer science; Data mining; Artificial intelligence; Computer vision; Optical pattern recognition; Education; Computer Science; Artificial Intelligence (incl. Robotics).; Pattern Recognition; Data Mining and Knowledge Discovery; Image Processing and Computer Vision; Computers and Education; Information Systems Applications (incl. Internet).